2018
DOI: 10.1093/cvr/cvy026
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced compliance: a novel adaptive biological mechanism following acute cardiac load

Abstract: We describe and translate to human physiology a novel adaptive mechanism, partly mediated by titin phosphorylation through cGMP-PKG signalling, whereby myocardial compliance increases in response to acute stretching. This mechanism may not function in the hypertrophic heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Finally, PTMs of titin that alter titin‐based myocardial passive stiffness represent a promising potential target for therapeutic intervention in HF patients with overly stiff hearts (such as in HFpEF), despite recent setbacks in some preclinical studies regarding to the role of cGMP‐PKG activation for myocardial stiffness in vivo . However, new approaches have already shown that titin phosphorylation and titin compliance can be increased in animal models by targeting various other intracellular pathways . Results of these studies suggest that the correction of mechanically relevant PTMs of titin in failing hearts can reduce pathological wall stiffness and normalize diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PTMs of titin that alter titin‐based myocardial passive stiffness represent a promising potential target for therapeutic intervention in HF patients with overly stiff hearts (such as in HFpEF), despite recent setbacks in some preclinical studies regarding to the role of cGMP‐PKG activation for myocardial stiffness in vivo . However, new approaches have already shown that titin phosphorylation and titin compliance can be increased in animal models by targeting various other intracellular pathways . Results of these studies suggest that the correction of mechanically relevant PTMs of titin in failing hearts can reduce pathological wall stiffness and normalize diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated rabbit cardiac muscle strips, pharmacological inhibition of NO signaling did not affect the decrease of passive tension in response to acute stretch. In contrast, this response was significantly reduced by blocking the actions of both NO and natriuretic peptides, an effect comparable to PKGI inhibition (14). Furthermore, in vivo, pharmacological activation of soluble guanylate cyclase did not influence ventricular compliance in normal and hypertrophied porcine hearts (15).…”
Section: Introductionmentioning
confidence: 91%
“…Titin is a mediator for mechano-sensory processes due to its ability to form multiple protein-protein interactions throughout the sarcomere (Kruger and Linke, 2009). The function of titin on passive tension is mediated by cyclic GMP-dependent PKG-mediated phosphorylation of several sites within the spring region of titin Leite-Moreira et al, 2018). PKG-mediated phosphorylation of titin at serine residue S469 alters the elasticity of N2B-unique sequence of titin, leading to reduced passive tension in human donor non-failing cardiac fibers .…”
Section: Titinmentioning
confidence: 99%